2021
DOI: 10.1108/bij-03-2020-0114
|View full text |Cite
|
Sign up to set email alerts
|

Governance modes in supply chains and financial performance at buyer, supplier and dyadic levels: the positive impact of power balance

Abstract: PurposeThis study analyzes whether power in the supply chain, based on governance modes and network centrality, explain financial performance at different levels of analysis: buyers, suppliers and dyads.Design/methodology/approachThe study employs a dual macro-micro lens based on global value chain (i.e. market, modular, relational and captive governance modes) and social network analysis (network centrality) to assess the impact of power (im)balance onto financial performance. Different from previous research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Moreover, we confirm that institutional voids may hinder sustainability and transparency: while Jestratijevic et al (2021) study showed 4 secretive out of 98 participants (∼4%), in the Brazilian sample, six out of 20 provided no sustainability information (∼30%). In line with the study by Marques et al (2021a) this shows that institutional voids allow firms to operate “below the radar” even when under scrutiny if there is no enforcement for sustainability compliance.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, we confirm that institutional voids may hinder sustainability and transparency: while Jestratijevic et al (2021) study showed 4 secretive out of 98 participants (∼4%), in the Brazilian sample, six out of 20 provided no sustainability information (∼30%). In line with the study by Marques et al (2021a) this shows that institutional voids allow firms to operate “below the radar” even when under scrutiny if there is no enforcement for sustainability compliance.…”
Section: Discussionsupporting
confidence: 81%
“…In the proportionality dimension, the emphasis on tier-1 suppliers suggests that fashion brands are not disclosing to the extent that there is threat to consumers. This results from the fact that most social risk lies beyond the brand and tier-1 suppliers (Marques et al , 2021a). Finally, regarding the actionability dimension, the study shows incipient best practices related to stakeholder engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Marques, Lontra, Wanke, and Antunes [3], positive buyer-supplier interactions may boost both manufacturer and supplier performance, as well as supply chain performance. To better understand the impact of buyersupplier interactions on SCM is crucial for two main reasons.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…There is already comprehensive literature on the diffusion of innovation focusing on adopting novel technologies (Currie & Spyridonidis, 2019;Lai 2017;Marques, Lontra, Wanke, & Antunes, 2021). However, such literature has been limited to the adoption of novel technologies only by consumers and focuses on describing the variables involved in user adoption (Cheng, 2016;Chu & Chen, 2016;Marangunić & Granić, 2015;Rahman, Lesch, Horrey, & Strawderman, 2017;Rondan-Cataluña, Arenas-Gaitán, & Ramírez-Correa, 2015;Scherer, Siddiq, & Tondeur, 2019;Williams, Rana, & Dwivedi, 2015).…”
Section: Introductionmentioning
confidence: 99%